2022
DOI: 10.1021/acs.est.1c04966
|View full text |Cite
|
Sign up to set email alerts
|

First Time Identification of Selenoneine in Seabirds and Its Potential Role in Mercury Detoxification

Abstract: Birds are principally exposed to selenium (Se) through their diet. In long-lived and top predator seabirds, such as the giant petrel, extremely high concentrations of Se are found.Selenium speciation in biota has aroused great interest in recent years, however there is a lack of information about the chemical form of Se in (sea)birds. The majority of publications focus on the growth performance and antioxidant status in broilers in relation to Se dietary supplementation. The present work combines elemental and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 83 publications
(224 reference statements)
0
5
0
Order By: Relevance
“…SeN has furthermore been shown to bind to myoglobin and hemoglobin to prevent auto-oxidation of iron (68) . SeN crosses the blood-brain barrier (78) and a recent study showed that the SeN can accumulate in the brains of giant petrels (69) . Authors suggest that SeN may play a role in the protection and function of the central nervous system.…”
Section: Case Study: Selenoneine and Se Status Among Nunavimmiutmentioning
confidence: 99%
See 1 more Smart Citation
“…SeN has furthermore been shown to bind to myoglobin and hemoglobin to prevent auto-oxidation of iron (68) . SeN crosses the blood-brain barrier (78) and a recent study showed that the SeN can accumulate in the brains of giant petrels (69) . Authors suggest that SeN may play a role in the protection and function of the central nervous system.…”
Section: Case Study: Selenoneine and Se Status Among Nunavimmiutmentioning
confidence: 99%
“…SeN was identified in 2010 in the blood of bluefin tuna at concentrations in the range of 5-40 μg Se/g. Despite this, following more than a decade of subsequent research, SeN has also been reported in different biological matrices of marine animal origin, including beluga whale mattaaq (8) , dolphins (66) , sea turtles (67) , various fishes (e.g., swordfish, Pacific mackerel, sardines, and tilapia) (68) , and seabirds (69) , indicating trophic transfer through marine food webs. When found in animals, SeN is likely derived from the diet as only some fungi and bacteria synthesize ergothioneine and SeN (65,70,71) .…”
Section: Case Study: Selenoneine and Se Status Among Nunavimmiutmentioning
confidence: 99%
“…The authors discussed different susceptibil-ity to Hg and/or parasites between males and females as well as the complexity of the antagonistic interactions of Hg and Se (Heinz & Hoffmann, 1998). When it comes to Hg detoxification in seabirds the potential role of selenoneine, the Se-analogue of ergothioneine should also be considered, because El Hanafi et al (2022) found a dramatic decrease of selenoneine with the increase of Hg concentration in the liver of giant petrels (Macronectes spec.). Sures et al (2017) reviewed a large number of studies which show that numerous species of digenea, cestoda, acanthocephala and nematoda accumulate organic pollutants and trace elements to a high extent.…”
Section: Burden With Trace Elementsmentioning
confidence: 99%
“…Other organic forms of Se, including selenouridine (SeU), which is synthesized by SelU and used to modify microbial nucleic acids 8,9 , and cofactors for some redox enzymes, such as molybdenum dehydrogenase 10,11 , have been identified in bacteria. In addition, selenoneine (SEN), a Se analog of ergothioneine, was found in various sea-dwelling animals and in β-proteobacteria [12][13][14][15] . With the exception that SEN could protect against mercury toxicity and act as an effective antioxidant 14,16,17 , little was known about its other physiological roles.…”
mentioning
confidence: 99%
“…In addition, selenoneine (SEN), a Se analog of ergothioneine, was found in various sea-dwelling animals and in β-proteobacteria [12][13][14][15] . With the exception that SEN could protect against mercury toxicity and act as an effective antioxidant 14,16,17 , little was known about its other physiological roles.…”
mentioning
confidence: 99%